Exploring the Impact of the PBL Learning Model on Students' Critical Thinking Proficiency - Ihsan Khoirul Anam; Herdien Raka Moch Isya; Imas Siti Masitoh; Ika Kartikasari (Universitas Pahlawan Tuanku Tambusai, 2023)
Based on the observation results, some teachers still utilize conventional learning models, which proving ineffective in enhancing students’ critical thinking abilities. This research aimed to analyze the impact of implementing the Problem-Based Learning (PBL) model on improvement of critical thinking skills. This study employs an experimental research method through quasi-experimental design (nonequivalent groups pretest-post-test design). Data collection involves tests, assignments, and performance demonstrations. The subjects in this study are students from class XI IPS 2, serving as the experimental group. Data analysis utilizes the Paired t-test and Simple Linear Regression. The research findings indicate that the average post-test scores surpass the average pretest scores. The paired sample obtained results reveal a Sig. (2-tailed) value of 0.000 < 0.05, indicating a disparity in the critical thinking skills of students in the experimental group before and after implementing the PBL learning model. Results of the regression analysis indicate a significance value of 0.032 < 0.05, which means that there is significant influence of using the Problem-Based Learning (PBL) model on students' critical thinking skills in the experimental class. Students' critical thinking skills experienced improvement after the use of Problem-Based Learning (PBL) model in the experimental class